Substrate Serving for Culture Optimization and Protease Productivity by Penicillium Notatum Strain on Deproteinised Foliage Extract from Lucerne and Beet - Jadhav, Rajesh K (The Asia Journal of Applied Microbiology, 2019)
When Penicillium notatum and Aspergillus niger grown on Lucerne DPJ by serving 1 % and 2 % of the substrates, viz., casein, starch and carboxymethyl cellulose (CMC), it showed the promising results of mycelial biomass and hydrolytic enzyme activities. Present attempt was on growth of species Penicilium notatum and Aspergillus niger on beet and lucerne foliage DPJ broth medium as compared with control glucose nitrate (GN) medium. Aspergillus niger not showed its growth on DPJ when enriched with casein and starch but there was growth on DPJ alone when substrates were not added. Therefore DPJ itself has the efficacy in initiating fungal growth. Beet DPJ inhibited the growth of Penicillium notatum when substrates were added, and only 1% of CMC was found responsible to initiate its growth by addition in DPJ. Penicillium notatum thrieved well on lucerne DPJ. Increasing concentration of casein in Lucerne DPJ enhanced rate of enzyme protease. Beet DPJ found having its antimicrobial influence. The objective of research was optimization of enzyme productivity by DPJ for industrial use.